Intervention Program to Improve Executive Functions and Enhance Planning Abilities of Patients With Mild Neurocognitive Disorder. Issue 5 (September 2019) - Fukuta, Daisuke; Mori, Chizuru
Abstract: Purpose: The aim of this study was to examine the effects of an intervention program to improve executive functions and enhance the planning abilities of patients with mild neurocognitive disorder. Design: A pilot intervention study. Methods: Ten inpatients performed an intervention program based on Lezak's conceptual model that teaches task-specific routines. The program consisted of six training sessions presented over a 2-week period. Neuropsychological assessments were performed pre- and postintervention. Findings: The postintervention scores of the Behavioral Assessment of Dysexecutive Syndrome Total Profile and two subtests were significantly higher than the preintervention scores. The instrumental Activities of Daily Living Scale and the Visual Analog Scale were significantly improved. Conclusion: This intervention program leads to improvement in the executive function of planning ability and promotes independence and self-confidence in patients with mild neurocognitive disorder. Clinical Relevance: Clinicians should consider the program in terms of improving the executive dysfunction, and the process of planning and the process of actual practice are important.